PENGGUNAAN SISTEM KLASIFIKASI DI UPT PERPUSTAKAAN POLITEKNIK NEGERI SRIWIJAYA PALEMBANG - Sipriani, Olga (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
In today's modern era characterized by increasingly rapid technological development, our need for information is also very important to support various aspects of life. This makes us an inseparable part of the information itself. Libraries according to the Law of the Republic of Indonesia No. 43 of 2007 are institutions that manage collections of written works, printed works, and / or recorded works professionally with a standardized system to meet the educational, research, preservation, information and recreational needs of the users. This research intends to find out more about the classification system used at the Sriwijaya State Polytechnic Library Palembang. This research uses qualitative research as the main research methodology. In UPT Perpustakaan Politeknik Negeri Sriwijaya Palembang, the data collection methods used were interviews, observations, and literature studies. According to the findings of a study, the classification system at the Palembang Sriwijaya State Polytechnic Library uses a digital system with the Electronic-Dewey Decimal Classification (E-DDC) 23rd edition application.